FAKTOR YANG MEMENGARUHI PERSEPSI MAHASISWA DALAM MENGGUNAKAN SOFTWARE AKUNTANSI SAAT PEMBELAJARAN JARAK JAUH - Aulia Salsabila; Dewi Febriani (Akuntansi dan Teknologi Informasi, 2022)
This study discusses the factors influencing students’ perceptions of using accounting software during distance learning. This study uses a descriptive quantitative approach. The data were obtained from questionnaires distributed to 134 students. SEM-PLS method with smartPLS was employed in this study. The result of this study states that distance learning has a negative effect on computer anxiety and computer anxiety itself negatively affects computer self-efficacy, perceived ease of use, and perceived usefulness. Computer self-efficacy has a positive effect on perceived ease of use. Perceived ease of use has a positive effect on perceived usefulness. This study examines only the factors influencing student perception and intention to use accounting software. This study provides empirical evidence on the effect of transactional distance and other factors such as computer anxiety and computer self-efficacy on perceptions of using accounting software. In addition, this research can enrich study materials or references for the future research.